Editorial to Special Interview Issue - Borimir Totev (Slovo, 2017)
It has been both a great challenge and an incredible honour to work on SLOVO Journal during such a thriving year for our awareness of Russian history and culture, marking the centenary of the Russian Revolution, but also a year that has tested the academic community’s ability to come together and defend its right to academic freedom. In the past year, we have produced two pronounced issues under VOL. 29 of SLOVO Journal, concentrating on the publication of interdisciplinary academic work of the highest standard. As an exclusively self-managed postgraduate project, and a unique part of the UCL Press family, we continue to provide some of the freshest insight into the Russian, East & Central European and Eurasian regions to our global readership. I’d like to repeatedly thank this year’s Editorial Board and the School of Slavonic and East European Studies for the precious amounts of time and dedication offered to SLOVO Journal. Read full text here.